Improved corrosion response of squeeze-cast AZ91 magnesium alloy with calcium and bismuth additions - Majhi J.; Ganguly S.; Basu A.; Mondal A.K. (My University, 2025)
The corrosion responses of the individual and combined Ca and Bi incorporated AZ91 alloy are investigated through the immersion, hydrogen evolution, and electrochemical tests. All the modified alloys exhibit better corrosion resistance than the base AZ91 alloy. The AZ91 + 1.0Ca (wt%) alloy unveils better corrosion resistance than the AZ91 + 0.5Bi (wt%) alloy owing to the Al2Ca phase formation. The combined Ca and Bi added AZ91 alloys acquire better corrosion resistance than the individual Ca or Bi added AZ91 alloys. The AZ91 + 2.0Ca + 0.5Bi (wt%) and AZ91 + 1.0Ca + 1.0Bi (wt%) alloys exhibit the lowest and the highest corrosion rates among the combined additions. © 2021 Elsevier B.V.